Implementasi Sistem Informasi Pembayaran SPP Berbasis Web (Studi Kasus : SMK Arrahman Tangerang) - Nur Azizah; Mohamad Warid; Arif Hidayatulloh (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
SPP payments still often experience problems such as data collection and the payment information process that has been used so far is still simple (semicomputerization) using only Microsoft Excel in inputting reports, therefore there are often problems in making reports for students in making spp payments required. precise and accurate so that it has not been able to produce a web-based SPP payment information system needed. In the current technological era, it is necessary to innovate the use of technology in the world of education to assist the administration of school finances so that the data collection and information process of Payments run effectively and efficiently. In this journal, we will discuss about designing a web-based SPP payment information system. This design aims to assist the finance department in recording SPP payments. The research method used is the SDLC type Waterfall method. This application helps the finance department in recording SPP payments.